Takhrij and Syarah Hadith Chemistry: Content, Benefits and Nutrition of Zam-zam Water in Everyday Life - Marsya Salsa Aulia; Rena Ajeng Triani; Yusuf Rohmatulloh; Ahmad Gibson Al Bustomi; R Yuli Ahmad Hambali (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet SAW. about zam – zam water. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The results and discussion of this research is zam-zam water, which is the water recommended by the Prophet Muhammad SAW as an antidote to disease during the time of the Prophet SAW. And already known by the world and research in the world. The conclusion of this study is that zam-zam water in the hadith has a very good content for health and is an antidote to disease and has been proven in modern research.